Konstruksi Kecantikan : Makna Cantik Oleh Mahasiswi Pengguna Skincare Korea: Konstruksi Kecantikan : Makna Cantik Oleh Mahasiswi Pengguna Skincare Korea - Harmona Daulay; Chintya Koestri Ayuningrum (UNIB Press, 2024)
This research aims to explore the beautiful construction that develops among female students who use Korean skincare products in the city of Medan. The research method used is descriptive qualitative with data collection methods through observation, in-depth interviews and documentation. The research results show that the definition of beauty varies greatly in the current era of globalization. For female Korean skincare users in Medan City, the construction of a beautiful reality occurs through three simultaneous stages: externalization, objectivation, and internalization. At the externalization stage, beauty is defined as physical appearance. The objectification stage revealed that the informants' knowledge about the concept of beauty was increasingly diverse. At the internalization stage, beauty is defined as a combination of visible physical beauty and inner beauty, which complement each other.